Evaluation of DNA Extraction Methods on Individual Helminth Egg and Larval Stages for Whole-Genome Sequencing - Doyle, Stephen R.; Sankaranarayanan, Geetha; Allan, Fiona; Berger, Duncan; Jimenez Castro, Pablo D.; Collins, James Bryant; Crellen, Thomas; Duque-Correa, María A.; Ellis, Peter; Jaleta, Tegegn G.; Laing, Roz; Maitland, Kirsty; et al. (Frontiers in Genetics, 2019)
Whole genome sequencing is being rapidly applied to the study of helminth genomes, including de novo genome assembly, population genetics, and diagnostic applications. Although late-stage juvenile and adult parasites typically produce sufficient DNA for molecular analyses, these parasitic stages are almost always inaccessible in the live host; immature life stages found in the environment for which samples can be collected non-invasively offer a potential alternative, however, these samples typically yield very low quantities of DNA, can be environmentally resistant, and are susceptible to contamination, often from bacterial or host DNA. Here, we have tested five low-input DNA extraction protocols together with a low-input sequencing library protocol to assess the feasibility of whole genome sequencing of individual immature helminth samples. These approaches do not use whole genome amplification, a common but costly approach to increase the yield of low-input samples. We first tested individual parasites from two species spotted onto FTA cards - egg and L1 stages of Haemonchus contortus and miracidia of Schistosoma mansoni - before further testing on an additional five species - Ancylostoma caninum, Ascaridia dissimilis, Dirofilaria immitis, Strongyloides stercoralis, and Trichuris muris - with an optimal protocol. A sixth species - Dracunculus medinensis - was included for comparison. Whole genome sequencing followed by analyses to determine the proportion of on- and off-target mapping revealed successful sample preparations for six of the eight species tested with variation both between species and between different life stages from some species described. These results demonstrate the feasibility of whole genome sequencing of individual parasites, and highlight a new avenue towards generating sensitive, specific, and information-rich data for the diagnosis and surveillance of helminths.